2000
DOI: 10.1007/s004280000199
|View full text |Cite
|
Sign up to set email alerts
|

Histological study on pN upgrading of oral cancer

Abstract: The International Union Against Cancer (UICC) does not define the number of sections required from each regional lymph node to record pTNM classification. This study was designed to clarify the incidence of occult metastasis and to assess the pN upgrading of patients with oral cancer. Ultimately, this study led to a proposal for appropriate semiserial sectioning guidelines. Five hundred fifty-four nonmetastatic cervical lymph nodes taken from 73 patients with oral cancer were subjected to hematoxylin-eosin (HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 22 publications
2
41
2
1
Order By: Relevance
“…This method has the advantage of preserving cellular and tissue morphological features, but is expensive and time-consuming, and therefore cannot be used for most routine applications . However, it has been demonstrated that it does not allow a significantly higher detection rate than histopathologic examination of HE-stained sections (Woolgar, 1999;Hamakawa et al, 2000b). In our study, immunodetection of carcinomatous cells of the 203 nodes that were HES negative and real-time RT -PCR positive was negative.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…This method has the advantage of preserving cellular and tissue morphological features, but is expensive and time-consuming, and therefore cannot be used for most routine applications . However, it has been demonstrated that it does not allow a significantly higher detection rate than histopathologic examination of HE-stained sections (Woolgar, 1999;Hamakawa et al, 2000b). In our study, immunodetection of carcinomatous cells of the 203 nodes that were HES negative and real-time RT -PCR positive was negative.…”
Section: Discussioncontrasting
confidence: 60%
“…As histopathologic analysis of neck dissection specimens is usually performed on several 3 -4 mm sections from each lymph node, and as micrometastases represent tumour deposits measuring less than 2 mm in diameter, they can be easily missed on routine light microscopy (Hermanek et al, 1999;Genden et al, 2003). For example, it has been reported that 21.9% of patients with cancer of the oral cavity have micrometastases with an average diameter of 1.36 mm (Hamakawa et al, 2000b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in molecular biology have improved diagnostics that were previously based on immunohistochemical procedures with a sensitivity of only 5-58% (average = 19.6%) [20]. Micrometastases are not infrequent with head and neck SCCs [19], and their reported occurrence in the oral cavity is 21.9% [22]. There is no consensus on the relevance of micrometastases to survival, but our recent studies indicate that prognosis is worse when micrometastases are present [23].…”
Section: Discussionmentioning
confidence: 99%
“…Barrera et al [25] reported the upstaging of 29 % of N 0 cases by IHC. Rhee et al [28] observed cervical micrometastasis in half of their patients with clinically N 0 head and neck cancer and Hamakawa et al [29] found micrometastasis in 15.9 % of N 0 necks, in oral cancer patients. Yoshida et al [30] had even better upstaging to report.…”
Section: Macrometastasesmentioning
confidence: 99%